Transaction Costs: A Conceptual Framework - Yousuf, Allam (International Journal of Engineering and Management Sciences, 2017)
Transaction Costs (TC) is a very important topic, especially in a changing work environment which has a large number of operational firms, and increasing business growth. The aim of this paper is to shed light on the transaction costs concept, and provide a conceptual framework to understand the meaning of transaction costs. Publications including articles and research papers have explained the notion of transaction costs and the theoretical issues related to them. The literature review reveals that, transaction costs are costs which arise because of the of a company‘s activities in the market , including (fees, commission, taxes) which are paid by the firm to provide a service or produce a good either to external parties or as internal costs. Therefore, according to the literature review. It emerges that firms must make a comparison between internal and external transaction costs and choose the lowest cost which enables them to increase profits. This means companies have to reduce transaction costs to the minimum level to achieve more profits and competitive advantage.